Photocatalytic Properties of MoS2 Deposited on Diatomite - Hu, Kun-Hong; Cai, Yong-Kui; Li, Qiu-Jing (Asian Journal of Chemistry, 2012)
A MoS2/diatomite composite was synthesized by depositing MoS3 on diatomite in a acidic solution and following calcination in H2. The obtained composite presented excellent photocatalytic activity on the degradation of methyl orange. The photocatalytic properties was influenced by the composition of the composite, the initial concentration of methyl orange, the amount of the catalyst and the pH value. The MoS2/diatomite composite is low-cost and can be reused for three cycles after filtration and drying. The MoS2/diatomite composite presents potential applications in the wastewater treatment.